Un jardin japonais botanique et médicinal de création récente - Manon Paul-Traversaz; Serge Krivobok; Michel Sève (Projets de Paysage)
A Japanese medicinal plant garden has been created in the botanical gardens of the faculties of Medicine and Pharmacy of Grenoble Alpes University. This garden is the result of an academic collaboration with Japan and highlights the plants that are used in the traditional Japanese medicine known as Kampo. The experiment carried out at the Dominique Villars Botanical Garden demonstrates that it is possible to reconcile the codes of the Japanese garden with the didactic approach of medicinal botany. By using characteristic elements of the landscape, the garden attracts the attention of visitors and provides a space for research partnerships and scientific reflection. The design of the garden, which is both innovative and modern, is intended for educational and recreational use. Special attention has been paid to the layout of the space and the features of the existing landscape and park. Recently added to the Dominique Villars Botanical Garden, this space contains close to a hundred Japanese botanical, ornamental and medicinal species.